Akcesornost zastavne pravice - Vrenčur, Renato (Pravni letopis, 2013)
The application of various instruments of collateral is required in business practice to strengthenthe position of creditors in the event of default by debtors, and in particular in bankruptcyor execution. Choosing appropriate collateral is even more important during a recession period,when businesses suffer from a chronic lack of liquidity and insolvency. Some collateral instruments are of a highly accessoriness nature (mortgage), while others constitute typical non-accessoriness collateral models. Understanding the above mentioned legal nature of the instruments is more than necessary for adequate selection and use of specific models in practice.
Keywords: hipoteka; terjatve; zavarovanje